INSTITUTIONAL GLOBALIZATION AS A SYSTEM OF INTEGRATION THE PHENOMENON OF THE POSTMODERN DEVELOPMENT - V. V. Zinchenko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. Institutionalism is gaining strength as a dominant point of view on the world. Its philosophical basis is the postulate of the uncertainty of the development, which comes to replace the neoclassical certainty characteristic of industrial society. The postulate of uncertainty is closely connected with the idea of subjectivization and individualization of post-industrial society. All these were very important components of the new paradigm, although they do not exhaust the problem. In the heart of postmodernism is a mass identity as a spiritual substance, while the more recently mass of people to realize themselves as natural and social beings. Person has absolute freedom in the acceptance and rejection of culture and civilization; it is pluralistic in their actions and in their consciousness. It is the subject of history and it should be creative, fluent mastering all the achievements of culture. Methodology. The dialogue system of the Postmodern, which is the basis of human communication with another person, human with society is a model of convergent formation of the world community and world economy. The same model of rationalism and adequate industrial society is a monologue, which is easily builds a bridge to violence, even if it is carried out in the name of the man behind him and the pathos of the exaltation of man as the bearer of unlimited creation possibilities. However, it is very important not just to modify rationalism, and to understand the origins of civilization. Scientific novelty. The postmodern era begins is not easy. Modern defending, using all their reserves: public thirst for justice, the priority of rationality (at least in the economy), monologist public agencies and politicians in contrast to the dialogic postmodern imperative modality in the spiritual existence of man instead the freedom. Finally, the world of the story is set a trap – the anthropological paradigm of the globalization ideology formation. In this paradigm, people see materialistic rational measure of space and society building, i.e. the natural and social being, not a spiritual person. All this was evident in the course of transformation in Ukraine. Its main weakness is obvious. This narrows the field of mass participation in the market or by the adopted symbolism, the field of subjectivity. The population is invited to wait and endure, i.e. plays the role of the object of political and economic manipulation. Even more unacceptable monopolization of subjectivity government, for which everything is regarded as a subject of state regulation. Conclusions. For civilization of cardinal feature is the treatment of the person as the subject of history. The need for the development of civilization to increase the degree of subjectivity in an economy where people can express themselves freely and responsibly through a system of private property relations: economic entity is the subject of property. Policy enhancing the role of human rights and the development of the principle of subjectivity means deepening the democratic foundations of the state structure. In the social sphere the subjectivity is expressed in the individualization of the social existence of man and the personification of public relations and it is implemented through the mechanisms of liberal institutions. It seems that the civilizational unity of the economy, democratic state and liberal society has the value of a scientific paradigm. Whatever the great cultural peaks of the postmodern, the main processes of a new society formed at its foot: in the area of formation of public consciousness and public preferences with the mass participation of the individual in the economy (involving the mass of the individual in social production on the level of financial relations, which allow the maximum extent possible to include in the economy of free choice), in the field of state-building and the formation of social institutions on the principles of Amateur participation.